Lucy Wilcox Adams: Early Advocate of Discussion-Based Adult Education - Susan Imel (Adult Education Research Conference, 2010)
The writings of Lucy Wilcox Adams as well as both historical and contemporary adult education literature were analyzed for the purposes of (1) examining the role of women in the development of the field; (2) discerning the development of Adams’ ideas regarding discussion-based adult education; and (3) comparing and contrasting her ideas with other literature.